Corrosion Study of Aluminum Alloy 3303 in Water-Ethylene Glycol Mixture: Effect of Inhibitors and Thermal Shocking. (10th January 2019) - Asadikiya, Mohammad; Zhong, Yu; Ghorbani, Mohammad
Abstract : Three types of corrosion inhibitors consisting of sodium diphosphate (Na2 H2 P2 O7 ), sodium benzoate (NaC7 H5 O2 ), and sodium tetraborate (Na2 B4 O7 ) were evaluated to analyze their effectiveness to inhibit the aluminum alloy 3303 (UNS A93303) against corrosion, in water-ethylene glycol (C2 H6 O2 ) mixture. Potentiodynamic polarization tests were carried out to study the effect of each chemical. The temperature of solutions was 88°C and the aluminum samples were coupled with five other metals consisting of mild steel, stainless steel, brass, copper, and solder to include the effect of galvanic corrosion. The results showed that sodium diphosphate can effectively protect the aluminum alloy 3303 in comparison with two other chemicals. The effect of thermal shocking on the corrosivity of water-ethylene glycol solution was also investigated. It was indicated that the corrosivity of water-ethylene glycol solution increases because of thermal shocking, which oxidizes the aqueous ethylene glycol. The corrosion rate of aluminum alloy 3303 coupled with the five metals in thermal shocked water-ethylene glycol solution is 142 mpy, while it is 94 mpy in fresh water-ethylene glycol solution.